Analisis kesesuaian nilai karakter cerita fiksi pada buku siswa kelas IV tema 8 sekolah dasar dengan nilai karakter kurikulum 2013 - Riza Ayu Ramadhani; Jenny Indrastoeti Siti Poerwanti; Sularmi Sularmi (Universitas Sebelas Maret, 2021)
The purpose of this study was to find out the suitability of fictional character values in Grade IV Student Book Theme 8 with 18 character values curriculum 2013. The research method used is descriptive qualitative with content analysis approach. The data and data sources in this study are fictions contained in the Grade IV Theme 8 Student Book. Data collection in this study uses observation techniques and document studies that are reduced to be then presented in instruments and verified. Based on the results of the research obtained that the value of characters that appear in fiction in the Book of Students Grade IV Theme 8 amounted to 14, namely: religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, respect for achievement, communicative pleasure friendly / proactive, care for the environment, social care, and responsibility. From the 14 character values, it can be known that the percentage of character appearance in fiction in The Grade IV Student Book Theme 8 is 77.78%. Based on the percentage obtained, it can be stated that the value of the characters in the fiction story in the Grade IV Student Book Theme 8 is appropriate.Keywords character values, fictional stories, Curriculum 2013, student book